Appropriate use of bisphosphonates in osteoporosis in cosenza health district (Italy). Issue 2 (12th March 2012) - Garreffa, M.; Piro, B.; Carbone, C.; Gallo, L.; Piro, D.; Reda, A.
Abstract : Background: Osteoporosis is a disease characterised by underdiagnosis and undertreatment. Persistence and adherence are an important problem in patients treated for osteoporosis. Purpose: To evaluate and monitor the use of bisphosphonates considering the appropriateness either with regard to the indication/limitation or to the persistence to the treatment. Materials and methods: The authors investigated the patients in Cosenza health district (Italy) in the years 2009 and 2010. The whole population is 291, 086 (51.3% women and 48.7% men). 9694 patients were treated with raloxifene, alendronic acid – alone or in association with cholecalciferol -, ibandronic acid, risedronic acid, strontium ranelate: 92.34% women and only 284 patients above 50 years old. Results: 56.2% of patients took raloxifene for less than 25% of the investigational period (six months); 11.9% took it for 25% – 50% of the investigational period (6-12 months); 18.9% took it between 50% and 75% of the time (12-18 months) and 13% took it for more than 75% of the time. Of the patients treated with alendronic acid, alone or in combination with cholecalciferol, 53.3% took the drug less than 25% of the investigational period, 13.3% for between 25% and 50%, 20.7% for between 50% and 75% and 12.7% took it for more than 75% of the time. 49.8% of the patients treated by ibandronic acid took the drug less than 25% of the investigational period, 13.4% took it between 25% and 50% of the time, 21.2% had it between 50% and 75% and 15.6% had it for more than 75% of the time. 52.2% of the patients treated by risedronic acid had the drug less than 25% of the investigational period, 12.6% had it between 25% and 50% of the time, 21.9% had it between 50% and 75% of the time and 13.3% had it more than 75% of the time. 75.8% of the patients treated by strontium ranelate took the drug less than 25% of the period studied, 9.6% took it between 25% and 50% of the time, 11.7% took it between 50% and 75% of the period studied and only 2.9% lasted for more than 75% of the time. Conclusions: Our observations confirm the underdiagnosis and the undertreatment of osteoporosis. Appropriate prescribing is the first step to adherence, the real target in chronic treatment.